2022
DOI: 10.1111/all.15230
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E response in health and disease beyond allergic disorders

Abstract: Immunoglobulin E is the latest discovered of immunoglobulin family and has been long associated with anaphylaxis and worm expulsion. Immunoglobulin E, along with mast cells, basophils, and eosinophils, is also a hallmark of type 2 immunity which is dysregulated in numerous diseases such as asthma, rhinitis, atopic dermatitis, and eosinophilic esophagitis in addition to anaphylaxis as aforementioned. However, recent advances have shed light on IgE regulation and memory explaining the low level of free IgE, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 197 publications
(265 reference statements)
0
26
0
2
Order By: Relevance
“…IgE can recognize exogenous antigens (Ags), facilitate antigen presentation via FcϵRI, trigger the degranulation of MCs and the release of multiple mediators, and regulate innate and acquired immunity. Several reports have shown that total serum IgE levels are significantly elevated in patients with psoriasis and that IgE + FcϵRI + cells are significantly increased in psoriatic lesions and decrease with the improvement of the disease ( 12 , 13 ). A non-classical IgE response may occur in psoriasis.…”
Section: Mast Cells In Psoriasismentioning
confidence: 99%
“…IgE can recognize exogenous antigens (Ags), facilitate antigen presentation via FcϵRI, trigger the degranulation of MCs and the release of multiple mediators, and regulate innate and acquired immunity. Several reports have shown that total serum IgE levels are significantly elevated in patients with psoriasis and that IgE + FcϵRI + cells are significantly increased in psoriatic lesions and decrease with the improvement of the disease ( 12 , 13 ). A non-classical IgE response may occur in psoriasis.…”
Section: Mast Cells In Psoriasismentioning
confidence: 99%
“…FCER2 gene is an 11-exon gene located at chromosome 19p13.3, encoding the low-affinity receptor for IgE (CD23) (32). CD23 interacts with IgE with low affinity, playing a dual role in regulating IgE synthesis in activated B lymphocytes and facilitating allergen-specific activation in T lymphocytes (33,34). Previous studies have demonstrated the role of FCER2/CD23 polymorphisms in exacerbations, lung function, regulation of IgE synthesis, and immunotherapy in asthma (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, multiple cardiovascular markers were also found to be raised in pediatric AD and they included E-selectin, an endothelial cell adhesion molecule, and several matrix metalloproteinases (MMP), which are proteins engaged in tissue remodelling [32]. Observations show that immunoglobulin E (IgE) may also play a role in cardiovascular homeostasis and disease; nevertheless, this idea is relatively new and poorly understood [33].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%